Accessible design and dementia: A neglected space in the equality debate. (January 2020) - Houston, Agnes; Mitchell, Wendy; Ryan, Kathy; Hullah, Nigel; Hitchmough, Paul; Dunne, Tommy; Dunne, Joyce; Edwards, Bethan; Marshall, Mary; Christie, Julie; Cunningham, Colm
This paper addresses the issue of accessible design in the context of dementia. It is not difficult to design buildings and outside spaces for people with dementia but you do have to follow clear design principles and values. However, unlike other disabilities, accessible dementia design is still viewed as an added extra and not a vital component of facilitating citizenship. In 2015, the World Health Organisation published guidance on human rights and dementia. People living with dementia are frequently denied their human rights even when regulations are in place to uphold them. This paper will focus on accessible design from a human rights perspective using the PANEL principles. PANEL stands for Participation, Accountability, Non-Discrimination and Equality, Empowerment and Legality. We will then conclude with recommendations for policy, practice and research to ensure that accessible design for people living with dementia does not continue to be a neglected space in the equality debate.